SUSTAINABLE BUSINESS DEVELOPMENT FROM THE ENVIRONMENTAL, SOCIAL AND GOVERNANCE CRITERIA PERSPECTIVE - Irina TODOS (Economica, 2022)
In the current economic context, concerns about environmental protection and the multiplication of the negative effects of industrial development on the environment have become particularly persistent. Environmental concerns have become particularly persistent, through the organization of various scientific events, which have laid the foundations for concepts such as sustainability/sustainable development, which promote human awareness, regarding the interdependencies between economic, political, natural and social phenomena, on a planetary level. The interest in environmental protection, addressing global problems of economic and social development, is on the agenda of the United Nations, which develops strategies and programs to solve them. The purpose of this work is to increase the degree of knowledge of the components of sustainable business development in ensuring a green business practice, thus, close knowledge of the ESG concept will allow companies to establish and prioritize their fields and activity policies.